Lattice Boltzmann Simulation of Nucleate Pool Boiling in Saturated Liquid (Communications in Computational Physics, 2020)
A thermal lattice Boltzmann method (LBM) for two-phase fluid flows innucleate pool boiling process is proposed. In the present method, a new functionfor heat transfer is introduced to the isothermal LBM for two-phase immiscible fluidswith large density differences. The calculated temperature is substituted into the pressuretensor, which is used for the calculation of an order parameter representing twophases so that bubbles can be formed by nucleate boiling. By using this method, two-dimensionalsimulations of nucleate pool boiling by a heat source on a solid wall arecarried out with the boundary condition for a constant heat flux. The flow characteristicsand temperature distribution in the nucleate pool boiling process are obtained.It is seen that a bubble nucleation is formed at first and then the bubble grows andleaves the wall, finally going up with deformation by the buoyant effect. In addition,the effects of the gravity and the surface wettability on the bubble diameter at departureare numerically investigated. The calculated results are in qualitative agreementwith other theoretical predictions with available experimental data.